Adherence to Iron-Folic Acid Among Pregnant Women Attending Antenatal Care in Southern Ethiopia, 2022 - Temesgen Geta Hardido; Adisu Ashiko Mikamo; Cherinet Tilahu Legesse (Mary Ann Liebert, 2023)
Background: Among the micronutrient deficiencies, iron and folic acid are the most common and frequently occur in pregnant women. So, the objective of this study was to assess the adherence to iron and folic acid among pregnant women booking antenatal services in the study area. Materials and Methods: A facility-based cross-sectional study design was used from January to April 2022. A structured questionnaire was used to collect data using systematic sampling techniques to approach 339 pregnant women. Data were entered and analyzed using SPSS software version 20. A descriptive analysis was performed. Adjusted odds ratios and corresponding 95% confidence intervals (CIs) were used, and statistical significance was reported at p-values <0.05 with 95% confidence. Results: In this study, 339 (99%) pregnant women participated. The mean age of the respondents was 28.04 years old, with a standard deviation of 5.3 years. The rate of adherence to iron and folic acid supplementation (IFAS) in pregnant women was 62.8%. Mothers under 19 years old (adjusted odds ratio [AOR]?=?0.025; 95% CI [0.003?0.218]), daily (AOR?=?0.127; 95% CI [0.028?0.568]), and those with a history of miscarriage (AOR?=?0.276; 95% CI [0.086?0.891]) were less likely to be using IFAS. However, greater knowledge of IFAS was positively correlated with use of the supplements (AOR?=?5.56; 95% CI [1.23?8.34]). Conclusions: In this study, the adherence rate with IFAS of pregnant women in the study area was 62.8%. This indicates that one in four women is not in compliance with IFAS. Appropriate counseling and health education should be provided to pregnant women to improve compliance.